Forms of lime application and use of phosphogypsum in low acid soil in southern Brazil: soybean-wheat yield and soil chemical properties - Besen,Marcos Renan (2021)
ABSTRACT Brazil is currently the leading country in no-till (NT) farming, particularly on Ferralsols (Latossolos), the most abundant soil type. These soils are characterized by subsurface acidity that cannot be effectively corrected by surface application of additives. In this situation, the use of phosphogypsum can be advantageous. This study aimed to assess the residual effects of lime and phosphogypsum application on a clayey Ferralsol, and four soybean and two wheat yields in southern Brazil. The area has been cultivated under no-till since 1975. The soil was limed to different base saturation (BS) levels (50, 60, 70, and 90 %) by surface application (SL) or lime incorporation (IL). Three combined treatments were also studied: (i) surface liming to 60 % BS plus standard (3.71 Mg ha-1) phosphogypsum dose (60G1), (ii) surface liming to 70 % BS + standard phosphogypsum dose (70G1); and (iii) surface liming to 70 % BS + double (7.42 Mg ha-1) phosphogypsum dose (70G2). Soil samples were collected 48 months after treatment. Soybean and wheat yield was not influenced by BS levels, however IL increased soybean yield in 2012/13, but reduced soybean and wheat yield in later crops. Phosphogypsum increased wheat yield by up to 12.8 % (2012 season) and 5.2 % (2015 season), but soybean was not influenced. Incorporated liming caused a decrease in soil Al3+ levels until 0.60 m depth, whereas SL decreased Al3+ levels until 0.30 m depth. Surface liming increased Mg2+ levels in the 0.40-0.60 m layer. Incorporated liming reduced soil organic matter in the surface layer. A double dose of phosphogypsum (7.42 Mg ha-1) had a greater residual effect in subsurface layers but caused a decrease in Mg2+ and K+ levels. Therefore, the standard phosphogypsum dose provided the best results. In the very clayey soil in subtropical environment, the effects of SL extend beyond surface layers and are preferable to those of IL, although production was not influenced by BS.